Cytomegalovirus: A Troll in the ICU? Overview of the Literature and Perspectives for the Future - Schildermans, Jolien; De Vlieger, Greet (Frontiers in Medicine, 2020)
Cytomegalovirus (CMV) is one of the most pathogenic viruses in human. After a primary infection, CMV resides in the host for life. When immunity is reduced, CMV can escape suppressive effects of the immune system and cause viremia and antigenemia. This reactivation has shown to impair outcome of solid organ and hematopoetic stem cell recipients. Therefore, international guidelines advise to prevent reactivation in transplant recipients by prophylactic or preemptive antiviral treatment. Nowadays, reactivation of the dormant virus has also been documented in nonimmunocompromised critically ill patients. Intriguing observational data have described the rate, the risk factors and the associated outcome of viral reactivation in this population. Despite the repetitively documented higher morbidity and mortality associated with CMV reactivation during critical illness, two trials did not find an association between CMV serostatus and intensive care unit outcome. In addition, proof-of-concept studies investigating prophylactic antiviral treatment to prevent this CMV reactivation during critical illness, failed to show a beneficial effect on interleukin levels or clinical outcome. Further research is necessary to resolve the question whether CMV replication impairs the prognosis in nonimmuno-compromised critically ill patients. We here propose strategies to unravel this question. First, post-mortem investigation may be useful to evaluate the effect of viral replication on impaired organs. Second, clinical and biochemical assessments may help to identify patients at high risk for reactivation. Third, preemptive treatment based upon detection of the virus is currently under investigation. Finally, newer antiviral agents or immune-stimulating biologicals may be beneficial in high-risk groups.